(untitled) (Salam International Academic Journal, 2025)
The objective of this study is to examine the key factors influencing migration from developing countries to developed nations. To this end, the research is framed within the push-pull theory of migration and employs a panel data model to analyze the impact of various factors on migration flows between these two groups of countries. The findings indicate that the geographical distance between origin and destination countries has a negative and statistically significant effect for both groups, suggesting that as the distance increases, migration to the destination country tends to decrease. The labor supply in the country of origin is found to be positive and significant for developing countries, but not significant for developed countries. The technological gap variable is negatively significant for developed countries, while it is positively significant for developing countries. In both groups, higher investment rates in the country of origin are associated with a decrease in migration; however, developing countries are more sensitive to this variable. Furthermore, variables such as per capita GDP differential, birth rate, human capital index, migration in the past two years, population size, and foreign direct investment in the country of origin are all positive and statistically significant for both groups. Among these, population and foreign direct investment exert a relatively smaller influence on shaping migration flows.